Kesadaran Hukum Gender dan Transformasi Sosial; Implementasi UU KDRT dalam Mengubah Pola Relasi Domestik di Indonesia - Zulfaidah, Rena; Sulastri, Dewi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
This study analyzes the implementation of Law No. 23 of 2004 on the Elimination of Domestic Violence (PKDRT Law) in the context of efforts to transform domestic relations and increase gender legal awareness in Indonesia. Domestic violence (DV) is a multidimensional issue rooted in gender inequality and reinforced by a culture of silence, even though data from the National Commission on Violence Against Women shows a significant increase in reported cases (15,652 cases in the domestic sphere in 2023). Using a normative-empirical legal approach with a focus on analyzing court decisions, this study found a significant gap between the spirit of the law and its practice in the field. The PKDRT Law aims to transform DV from a private matter into a public criminal offense. However, its implementation faces strong cultural, social, and institutional challenges, including stigma against victims, pressure to reconcile for the sake of “family unity,” and a lack of holistic understanding of gender justice among law enforcement officials. Analysis of court decisions, such as Supreme Court Case No. 1583 K/Pid.Sus/2019 and Gresik District Court Case No. 139/Pid.Sus/2019/PN.Gsk, reveals a tendency for judges to impose minimal sentences or be influenced by social pressure, which ultimately distorts justice for victims and reduces the transformative power of the law. This study concludes that the existence of regulations alone is not enough; a shift in collective consciousness and gender-sensitive implementation are needed to realize equal domestic relations.